2009
DOI: 10.1002/cphc.200900010
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Oxidation by the Superoxide Radical: A Theoretical Study

Abstract: The cysteine residue oxidation by the superoxide radical in the gas phase and in aqueous solution is studied using the integrated molecular orbital+molecular orbital (IMOMO) method combining the quadratic configuration interaction [QCISD(T)] and density functional (DFT) methods. The molecular environment effects are systematically investigated by considering two alternative directions of attack of the superoxide radical on the thiol and two different cysteine residue conformations. It is found that hydrogen bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 23 publications
3
3
0
Order By: Relevance
“…Overall, our mass spectrometric studies confirm that DA and its derivatives are capable of oxidizing Aβ (especially, at M35) with and/or without Cu(II) under aerobic conditions via their oxidative transformation, which could be the source of their observed antiamyloidogenic activity. Note that (i) our results did not exhibit the formation of transformed DQ−protein adducts, as proposed in the previous studies (structure of DQ is shown in Figure 1b); 2,15,51 (ii) histidine residues (i.e., H13 and H14), 45,49,51 along with M35, could not be ruled out as oxidation sites.…”
Section: •−supporting
confidence: 69%
“…Overall, our mass spectrometric studies confirm that DA and its derivatives are capable of oxidizing Aβ (especially, at M35) with and/or without Cu(II) under aerobic conditions via their oxidative transformation, which could be the source of their observed antiamyloidogenic activity. Note that (i) our results did not exhibit the formation of transformed DQ−protein adducts, as proposed in the previous studies (structure of DQ is shown in Figure 1b); 2,15,51 (ii) histidine residues (i.e., H13 and H14), 45,49,51 along with M35, could not be ruled out as oxidation sites.…”
Section: •−supporting
confidence: 69%
“…This also indicated that although cysteine redox-sensitivity is mainly affected by protein structural environment as revealed by some previous studies [3941], redox-sensitive cysteines can still be inferred using only sequence features with moderate accuracy. Sequence-based prediction is much more advantageous in that it is not limited by structure data thus can be widely used for prediction as long as the protein sequence data is available.…”
Section: Resultssupporting
confidence: 65%
“…In addition, it has been reported that cysteine can be modified by superoxide (10). Therefore, we hypothesized that ASA-induced increases in superoxide production might modify the cysteine residue of the ZO-1 protein.…”
Section: Discussionmentioning
confidence: 95%